PERANGKAT LUNAK PRESENSI FOTO DAN GEO LOCATION BERBASIS PROGRESSIVE WEB APP - Sehab, Assyfa Ibnu; Sofian, Rudy; WK, Wahyu Nurjaya; Pakpahan, Andy Victor; Ferdiansyah, Fahmi Reza (Jurnal Teknologi Informasi, 2025)
The development of information technology demands that companies improve operational efficiency, including in employee attendance systems. Conventional attendance methods have weaknesses such as the risk of data manipulation and difficulties in real-time monitoring. PT. Primasaga Sinergia Indonesia faces this challenge with an inefficient manual attendance system. This research designs and develops an attendance information system based on PWA (Progressive Web App) with photo and geolocation features to address the issue. This application aims to improve the accuracy and efficiency of attendance, as well as provide ease of monitoring for management. The results are expected to improve efficiency and accuracy in the management of employee attendance at PT. Primasaga Sinergia Indonesia.